2011
DOI: 10.1038/ni.2104
|View full text |Cite
|
Sign up to set email alerts
|

Human IL-25- and IL-33-responsive type 2 innate lymphoid cells are defined by expression of CRTH2 and CD161

Abstract: Innate lymphoid cells (ILCs) are emerging as a family of effectors and regulators of innate immunity and tissue remodeling. Interleukin 22 (IL-22)- and IL-17-producing ILCs, which depend on the transcription factor RORγt, express CD127 (IL-7 receptor α-chain) and the natural killer cell marker CD161. Here we describe another lineage-negative CD127(+)CD161(+) ILC population found in humans that expressed the chemoattractant receptor CRTH2. These cells responded in vitro to IL-2 plus IL-25 and IL-33 by producing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

70
1,108
2
9

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 1,039 publications
(1,189 citation statements)
references
References 38 publications
70
1,108
2
9
Order By: Relevance
“…For the development and function of human and mouse ILC2, the transcription factors GATA3 and RORα are essential 17. In the peripheral blood, the majority of CD127 + ILC are ILC2, additionally, group 2 ILC have been found in the healthy human lung 2, 18 and in the skin 19, 20. An updated view on ILC2 function in pulmonary and dermal inflammatory diseases is provided elsewhere 21.…”
Section: Ilc Subsetsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the development and function of human and mouse ILC2, the transcription factors GATA3 and RORα are essential 17. In the peripheral blood, the majority of CD127 + ILC are ILC2, additionally, group 2 ILC have been found in the healthy human lung 2, 18 and in the skin 19, 20. An updated view on ILC2 function in pulmonary and dermal inflammatory diseases is provided elsewhere 21.…”
Section: Ilc Subsetsmentioning
confidence: 99%
“…An updated view on ILC2 function in pulmonary and dermal inflammatory diseases is provided elsewhere 21. In humans, ILC2 are abundant in nasal polyps of patients with chronic rhinosinusitis (CRS) and in bronchoalveolar lavage (BAL) of idiopathic pulmonary fibrosis patients 18, 22. In the skin, increased presence of ILC2 is associated with atopic dermatitis both in human and mouse as reviewed elsewhere 21.…”
Section: Ilc Subsetsmentioning
confidence: 99%
“…These cells were further distinguished by their capacity for producing type-2 cytokines (mainly IL-5 and IL-13) in response to IL-2, IL-25 and/or IL-33, which contributed to their ability to mediate their roles in gut parasite clearance. Importantly, an IL-25/IL-33-responsive ILC2 population was also identified in human lung and gut by Spits and colleagues (Mjosberg et al 2011). …”
Section: Identification and Characterization Of Ilc2mentioning
confidence: 90%
“…This effect was mediated by ILC2-derived IL-13, since adoptive transfer of wild-type ILC2 into infected il13 -/-mice was sufficient to restore viral-induced AHR in these otherwise AHR-resistant mice (Chang et al 2011). Whilst the physiological role of ILC2 in human airway inflammation is not fully understood, ILC2 were shown to be elevated in nasal biopsies of chronic rhinosinusitis patients as compared to healthy controls (Mjosberg et al 2011) demonstrating an association of these cells with human disease. Moreover, a recent report has shown that the prevalence of ILC2 in the blood of allergic asthma patients was substantially higher than either allergic rhinitis patients or healthy controls (Bartemes et al 2014).…”
Section: Role Of Ilc2 In the Pathogenesis Of Allergic Inflammationmentioning
confidence: 98%
“…Ces cellules expriment le récepteur CRTH2 (chemo-attractant receptor homogous molecules expressed on TH2) et produisent de l'IL-13 en réponse à l'IL-2 et à l'IL-33. Ces cellules sont également présentes au niveau de polypes prélevés chez des patients atteints de rhinosinusite chronique, une pathologie qui se caractérise par une inflammation induite par les cytokines de type 2 [17]. En outre, des essais cliniques de blocage de l'IL-13 par un anticorps monoclonal, menés chez des patients asthmatiques, ont montré une efficacité relative [18].…”
Section: Les Ilc2 Chez L'hommeunclassified